1998
DOI: 10.1063/1.120827
|View full text |Cite
|
Sign up to set email alerts
|

Existence of two-dimensional absolute photonic band gaps in the visible

Abstract: Using the plane wave method, we study two two-dimensional structures that possess absolute photonic band gaps: the triangular and the graphite photonic crystals. We compare their convenience in achieving photonic crystals which inhibit the propagation of visible electromagnetic waves. We show that this is very difficult to obtain with a triangular structure because its gap is too narrow and its dimensions are too small to be fabricated. On the contrary, wider gaps and larger dimensions that can easily be etche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Assume the dielectric modulation to be only on the z -y plane and in-plane wave propagation. The structure consisting of parallel, infinitely long air cylinders in a dielectric background, arranged in a triangular lattice, was shown to be the optimal case [37], together with the one consisting of dielectric cylinders in air arranged in the graphite structure [38]. Experiments done in the microwave regime [39,40] showed excellent agreement with the theoretical predictions.…”
Section: Photonic Band Gap Materialssupporting
confidence: 71%
See 1 more Smart Citation
“…Assume the dielectric modulation to be only on the z -y plane and in-plane wave propagation. The structure consisting of parallel, infinitely long air cylinders in a dielectric background, arranged in a triangular lattice, was shown to be the optimal case [37], together with the one consisting of dielectric cylinders in air arranged in the graphite structure [38]. Experiments done in the microwave regime [39,40] showed excellent agreement with the theoretical predictions.…”
Section: Photonic Band Gap Materialssupporting
confidence: 71%
“…for a triangular arrangement of air cylinders in dielectric [37] and for a graphite arrangement of solid dielectric cylinders in air [38].…”
Section: E(f)mentioning
confidence: 99%
“…The electromagnetic wave propagation inside a PC is forbidden for some specific or all directions for a certain frequency range due to the photonic bandgap (PBG) effect [1]. However, it has been reported that there is anisotropy of PBG in PC caused by the low-level rotational symmetry in its Brillouin zone [2], [3]. Higher rotational symmetry leads to more circular Brillouin zone and less anisotropy of PBG.…”
mentioning
confidence: 99%
“…This would provide the ideal PBG structure for the use in applications where the inhibition of spontaneous emission is desirable. It is firmly established that periodic triangular and hexagonal lattice structures can support complete photonic bandgaps in 2D and 3D [4][5][6]. However, complete and absolute PBGs (CAPBGs) have only been achieved in very high dielectric constant materials like GaAs (m= 13.6) using hexagonal lattice structures [6].…”
Section: Introductionmentioning
confidence: 99%
“…For many applications involving the use of PCs it is desirable to acquire complete and absolute photonic bandgaps [4]. In the case of such PBG structures, the wave propagation is forbidden for any direction of propagation, and independent of the polarisation state.…”
Section: Introductionmentioning
confidence: 99%